Green Synthesis of Magnesium Oxide Nanoparticles Using Brassica oleracea and Punica granatum Peels and their Anticancer and Photocatalytic Activity - Sugirtha, P.; Divya, R.; Yedhukrishnan, R.; Suganthi, K.S.; Anusha, N.; Ponnusami, V.; Rajan, K.S. (Asian Journal of Chemistry, 2015)
Experiments were carried out on the synthesis of magnesium oxide nanoparticles using the water extract of cauliflower and the water extract of pomegranate peels. The primary particles were of sizes 30-45 and 50-65 nm in the powder synthesized using the water extract of cauliflower and the water extract of pomegranate peels respectively. Polycrystalline powders were obtained when synthesis was carried out using the water extract of pomegranate peels, white crystalline powders were obtained when using the water extract of cauliflower. The green-synthesized magnesium oxide nanoparticles exhibited good anticancer activity, with 31.2 μg/mL being the nanoparticles concentration required for destruction of 50 % of HeLa cells. The green-synthesized magnesium oxide nanoparticles were found to possess photocatalytic activity both under UV irradiation and sunlight.